Description, DNA barcoding and phylogenetic placement of a remarkable new species of Eopelma (Hymenoptera: Eupelmidae) from Borneo - Fusu, Lucian; Polaszek, Andrew (Zootaxa, 2017)
Eopelma gibsoni sp. nov. is described based on a male recently collected in Borneo. It is the second species of the genus to be described, and the first species of chalcid wasp in which a pattern of dark stripes on the compound eye is described. The presence of similar dark stripes on the eyes of other chalcid wasps is discussed, highlighting the importance of citizen science. The description is accompanied by a DNA barcode sequence to assist future identification and association of the sexes. The phylogenetic position of E. gibsoni based on 28S DNA sequences is discussed.